Determinants of bank profitability in China - Gao, Xiaohong (2019)
This paper empirically analyses the determinants of the profitability of Chinese commercial banks from 2008 through 2018. The sample consists of 90 commercial banks which including 5 state-owned banks, 8 joint-stock banks, 74 small and medium-sized banks (SMBs) and 3 foreign banks. Pooled OLS, the fixed effect model, the random effect model and the system GMM model are the methods that have been used in this study. The discussion about results mainly focuses on the fixed effect model and the system GMM estimator because they are more appropriate than other methods. Empirical results present that bank size, efficiency, asset quality，unemployment rate and inflation have a significant impact on Chinese banks performance, and unemployment rate and inflation are positively related to banks profitability among other variables. Liquidity can only be considered as an important factor of profitability when the equation is measured by ROAE, and the relationship is negative. The differences of results measured by fixed effect model and the system GMM is GDP growth rate has no impact on ROAE in system GMM model and Z-score only have an impact on ROAA. In addition, this study also concludes that state-owned banks and joint-stock banks are outperform SMBs and foreign banks considering the support of state policy and size of the bank.